Glaciers law: discussions and controversies about environmental federalism (Papeles, 2022)
The Argentine National Constitution assigns to the Nation the function of pass norms that contain the minimum standards for environmental protection, and to the Provinces the function of pass the necessary norms to complement them (art. 41 CN), which can grant greater environmental protection but never lower than the minimum federal standards. Furthermore, it establishes that the provinces have the original domain of the natural resources found in their territory (art. 124 CN). The objective of this work is to analyze the discussions and controversies about environmental federalism that were generated during the processes of sanction and implementation of Law 26,639 of Minimum standards for the Preservation of Glaciers and the Periglacial Environment. This norm establishes the criteria for the protection of these ecosystems to preserve them as strategic reserves of water resources and prohibits mining activity in these areas. The discussions for the Glaciers Law have been crossed by the federalization/centralization dichotomy and the tensions due to the application of articles 41 and 124 CN. During this process, disputes (re)emerged between pro,mining actors and environmentalists/anti,extractivists regarding provincial autonomy over the domain, use and management of natural resources.
Keywords: Glaciers Law; environmental federalism; mining